PENYULUHAN USAHA AGRIBISNIS PEDESAAN KEPADA WANITA KELOMPOK TANI (WKT) DI DESA KARANG BINDU, PRABUMULIH. - Emilda, Emilda (Jurnal Abdimas Musi Charitas, 2020)
Karang Bindu Village is one of the villages in Rambang Kapak Tengah District, Prabumulih, where most of the people have a livelihood as rubber farmers. Health care facilities in Karang Bindu Village are increasingly limited, only puskesmas are available and besides the cost of treatment is also increasingly expensive. There are several organizations in Karang Bindu Village among other Women Farmers Groups. However, the role of Women Farmers Groups in Karang Bindu Village is still not optimal compared to other villages. This can be seen from the addition of the use of the yard. Counseling about rural agribusiness for Women Farmer Groups in Karang Bindu Village is expected to provide knowledge about types of medicinal plants and their benefits, increase knowledge of procedures for growing Family Medicinal Plants (TOGA), provide knowledge about marketing and provide knowledge of making simple financial statements.